2016
DOI: 10.1093/mnras/stw1071
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution optical imaging of the multiple T Tauri system LkHα 262/LkHα 263

Abstract: We report high spatial resolution i' band imaging of the multiple T Tauri system LkHα 262/LkHα 263 obtained during the first commissioning period of the Adaptive Optics Lucky Imager (AOLI) at the 4.2 m William Herschel Telescope, using its Lucky Imaging mode. AOLI images have provided photometry for each of the two components LkHα 263 A and B (0.41 arcsec separation) and marginal evidence for an unresolved binary or a disc in LkHα 262. The AOLI data combined with previously available and newly obtained optical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…The simulation package that we have created is based on the original work and the Matlab kernel from Marcos van Dam and collaborators (van Dam & Lane, 2002). It allows many of the important parameters that are used to be adjusted.…”
Section: Example Instrumental Configurationmentioning
confidence: 99%
See 3 more Smart Citations
“…The simulation package that we have created is based on the original work and the Matlab kernel from Marcos van Dam and collaborators (van Dam & Lane, 2002). It allows many of the important parameters that are used to be adjusted.…”
Section: Example Instrumental Configurationmentioning
confidence: 99%
“…Following the work of van Dam & Lane (2002) we have based our wavefront recovery algorithms on the use of Radon transforms. These have seldom been used in astronomical applications (though see Starck et al, 2003) but are very well studied and widely used in, for example, x-ray computerised tomography systems where they are particularly successful.…”
Section: Wavefront Processing Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that speckle imaging algorithms benefit from working on short-exposure observations from AO-assisted instruments. For instance, the lucky imaging technique benefits as the fraction of lucky images increases due to the AO correction, as, e.g., Velasco et al (2016) have tested this on AO-assisted i -Band observations from AOLI (e.g. Velasco et al 2018) mounted on the 4.2 m William Herschel Telescope, and Law et al (2009) have used the LAMP instrument on the 5 m Palomar Hale telescope to achieve good image cosmetics.…”
Section: Introductionmentioning
confidence: 99%